Pancasila in the Context of the History of the Struggle of the Indonesia Nation - Resti Lestari; Ezra Chynthia; Lasniroha Situmorang; Nurmala Sandra; Insi suci Mahrika; Intan Dwi Putri; Masduki Akbari; Agus Purwanto (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
This study aims to explore the root of Pancasila as national ideology of Indonesia. Two research questions arised: 1) what kind of cultural root of Pancasila in the life of Indonesian people; 2) what kind of processes of Indonesian leaders in formulating Pancasila. Method used is webinar via zoom meeting . The results show that many parts of Pancasila have to be culture of Indonesian. On the other hand, reconstruction of formulating Pancasila has to be deviated by political power of interest group. Nugroho Notosusanto as the New Order historian wanted to de-Soekarnoization through heroificated Muhammad Yamin as Pancasila discoverer.